Tissue Culture Technology for Rural Agriculture Development: A case study in Hambantota - Hirimburegama, Kshanika; Nishantha, H.N.G.; Hirimburegama, W.K. (My University, 2012)
Wthe topic "tissue culture technology for rural agriculture development: a case study in WMhimbantota'' was selected because of the importance of adopting biotechnology in our i mm try, where agriculture is still the main income of the rural sector and Agric - mproducer/ the farmer, is faced with open economy, globalization and with WTO trade WNtlicies but hardly with any modern biological/agricultural technology for food 'induction. ssue culture technology is a soil-less type of growing and can be defined as "Growth of lunts cells, tissues, organs or organisms in an aseptic condition on an artificial medium fjft a glass or plastic vessel". Globally, tissue culture technology has advanced to such an %tlent that it is now recognized as a multi billion $ industry. Mugampura Agrotechnology & Community Service Center, University of Colombo located in a rural sector at Weligatta, Hambantota (250 km from Colombo) is an ongoing project to assist rural development through science & technology, especially agrohiotechnology. This project is the first ever kind developed by a University system in Sri I unka in collaboration with Government & other organizations. hloin Objectives of the project are for University to play a direct role in directing ili-velopment activities of the rural sector of the country and to fulfill one main responsibility of universities - Extension/Community services, while being engaged in I inching and R&D. The universities and researchers are linked through the center, Willi the community for an effective transfer of science/knowledge & technology. The (I/tempt is to educate & empower especially the women and thereby to achieve rural 0dor development.